(untitled) - Nguyễn, Đình Chú (Hà Nội, 1999)
Nội dung sách bao gồm 2 phần: Phần 1: Văn học dân gian; Phần 2: Văn học Việt Nam từ thế kỉ thứ X đến hết thế kỉ XIX.
Keywords: Rhetoric,Vietnamese literature,Vietnamese literature; Study and teaching (Secondary),History and criticism,Study and teaching (Secondary)